Representações sobre os cursos de engenharia do Centro Federal de Educação Tecnológica de Minas Gerais CEFET-MG - Barata, Vania Cristina Machado (2010)
This study aims to know the present representations of the engineering courses of the Federal Center of Technological Education of Minas Gerais (CEFET-MG), situated in Belo Horizonte. It focuses on the school drop-out and seeks to identify the factors which have caused it as well as the reasons why the students, after passing the entrance exams, give up studying there. The research focuses on three courses: Electrical Engineering, Mechanical Engineering and Civil Production Engineering. Our hypothesis is that, in the social imaginary, CEFET-MG has not reached legitimacy as an institution of undergraduate education yet. For this purpose, the historical origin of CEFET-MG is reviewed and there is a debate about the undergraduate education in the context of the Brazilian reality. The central focus of the research is based on the concept of social representation , mainly the theory of Pierre Bourdieu, among others. The qualitative methodology is used, and the semi-structured interview is the main source to the knowledge of the problem studied